THE INFLUENCE OF DER, CR, NPM ON STOCK PRICES AND RUPIAH EXCHANGE RATES AS MODERATING VARIABLES - Putra, Aldo Achmad; Purnamasari, Vidya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This research was conducted to analyze the factors that influence stock prices like DER, CR, and NPM which are moderated by the Rupiah exchange rate. The approach used is quantitative with panel data from banking companies indexed in LQ-45 from March 2017 to March 2023. Using Random Effect Model (REM) and Moderated Regression Analysis (MRA) analysis. The results show that DER, CR, and the Rupiah exchange rate affect stock prices. Also, the Rupiah exchange rate can weaken DER in influencing stock prices and strengthening CR in influencing stock prices. This research is a study that adds the Rupiah exchange rate as a moderator variable which proves that the Rupiah exchange rate is able to moderate DER and CR in influencing banking stock prices. The results of the study provide information and insight for decision makers and investors in banking companies that DER, CR and Rupiah exchange rates can influence banking stock prices. Therefore, investors pay attention to these factors before investing in banking companies. The limitation of this research lies in the research object which is only devoted to LQ-45 indexed banking companies.